AOU Policlinico di Bari - West China Hospital of Sichuan University. Global experience of medical profession, battle, health, friendship against COVID -19 - Carlucci , Matilde; Carpagnano, Lucia Federica; Serrone, Nicola; Dimatteo, Tiziana; Migliore, Giovanni (Acta Biomedica Atenei Parmensis, 2020)
Background: The global context we are experiencing, characterized by the pandemic spread of SARS-CoV2, imposes strict containment, isolation and physical distance measures, necessary to control and contain the risk of contagion. Despite social distances and isolation in this context of threat to Global Health, the sharing of experiences, professionalism, scientific research and Public Health strategies is fundamental. Never before has telemedicine played a decisive role in supporting the healthcare organization, The University Hospital Consortium Policlinico of Bari has launched an experimental partnership project with West China Hospital of Sichuan University through periodic and scheduled video conferences. Materials and Methods: The Company Strategic Management, the Dean of the Faculty of Medicine and Surgery of the University of Bari, Medical Executives of the Health Department, of the U.O of Infectious Diseases, Anesthesia and Resuscitation, Pulmonology, Emergency, Hygiene, Occupational Medicine, Psychiatry and Doctors Resident operating in the COVID Area. are involved in the Experimental Project., all adequately trained and instructed on the operating protocol. Results: From the preliminary data of this study, it appears that the Bari Polyclinic has adopted the same therapeutic strategies started in China in the previous months, believing early diagnosis and treatment to be a strength in the battle against COVID-19. The project makes it possible to make the management of COVID-19 patients optimal, safe and better, using the experience acquired in the field by Chinese doctors who, first caught by this health emergency, have obtained positive results.